IOS forensics cookbook : over 20 recipes that will enable you to handle and extract data from iOS devices for forensics /: over 20 recipes that will enable you to handle and extract data from iOS devices for forensics. (2016) - Birani, Bhanu; Birani, Mayank
No abstract available